2024
DOI: 10.3390/mi15040494
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Tensile Properties, and Fracture Toughness of an In Situ Rolling Hybrid with Wire Arc Additive Manufacturing AerMet100 Steel

Lei Lei,
Linda Ke,
Yibo Xiong
et al.

Abstract: As a type of ultra-high strength steel, AerMet100 steel is used in the aerospace and military industries. Due to the fact that AerMet100 steel is difficult to machine, people have been exploring the process of additive manufacturing to fabricate AerMet100 steel. In this study, AerMet100 steel was produced using an in situ rolling hybrid with wire arc additive manufacturing. Microstructure, tensile properties, and fracture toughness of as-deposited and heat-treated AerMet100 steel were evaluated in different di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This Special Issue covers a wide range of forming materials, including zirconium alloys [ 24 ], titanium alloys [ 20 , 23 ], steel [ 21 , 25 , 26 ], composites (e.g., electroless copper and carbon fiber [ 27 ]), and in particular, metallic multi-materials (e.g., copper/silver [ 22 ]), 4D printing materials (e.g., NiTi, smart materials for soft interactive hydrogel [ 19 ]).…”
Section: Materials Of Laser Additive Manufacturing In Special Issuementioning
confidence: 99%
See 3 more Smart Citations
“…This Special Issue covers a wide range of forming materials, including zirconium alloys [ 24 ], titanium alloys [ 20 , 23 ], steel [ 21 , 25 , 26 ], composites (e.g., electroless copper and carbon fiber [ 27 ]), and in particular, metallic multi-materials (e.g., copper/silver [ 22 ]), 4D printing materials (e.g., NiTi, smart materials for soft interactive hydrogel [ 19 ]).…”
Section: Materials Of Laser Additive Manufacturing In Special Issuementioning
confidence: 99%
“…Lei et al [ 21 ] reported that AerMet100 steel was produced using an in situ rolling hybrid with wire arc additive manufacturing. In their work, the microstructure, tensile properties, and fracture toughness of as-deposited and heat-treated AerMet100 steel were evaluated in different directions.…”
Section: Materials Of Laser Additive Manufacturing In Special Issuementioning
confidence: 99%
See 2 more Smart Citations